PREPARATION AND EVALUATION OF CONTROLLED RELEASE FLOATING MICROSPHERES OF REPAGLINIDE: OPTIMIZATION AND IN-VITRO STUDIES - Sharma, Megha; Kohli, Seema; Pal, Abhisek (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To develop and evaluate floating microspheres of repaglinide (RG). Materials and Methods: RG loaded noneffervescent microspheres of different ratios of ethylcellulose (EC) and hydroxypropyl methylcellulose (HPMC K4M) were prepared using polyvinyl alcohol as emulsifier by solvent evaporation technique. Various process variables such as polymer ratio, stirring speed, concentration of drug, and emulsifying agent were studied. Compatibility of drug and polymers was studied by Fourier-transform infrared spectroscopy (FTIR). Characterization, in-vitro evaluation, and kinetic studies were performed. Results: FTIR spectra have revealed no drug-excipient incompatibility. The average particle size of microspheres was in the range of 312-359 Î¼m. The results showed that floating microspheres were successfully prepared with good yield (56.15-64.3%), high entrapment efficiency (58.22-70.14%), and good floating behavior (63.1-76.2%), respectively. In-vitro release data indicates appreciable amount of drug is released (62.28-73.27%) from the microspheres in gastric fluid. The mechanism of drug release founds to follow first order kinetics (r2=0.986). Conclusion: The developed floating microspheres of RG may be used for prolonged drug release for at least 12 hrs, thereby improving bioavailability and patient compliance. Keywords: Repaglinide, Compatibility, Kinetic, Ethylcellulose.